Manajemen Pembelajaran Kitab Kuning di Sekolah Tinggi Kitab Kuning - Aulia, Ina; Antariksa, Walid Fajar (Ar-Rosikhun: Jurnal Manajemen Pendidikan Islam, 2022)
Pesantren is an educational institution in Indonesia that uses the classical book as a reference for learning. The classical book contains the contents of various sciences that guide Muslims in their live. Islamic boarding schools are currently facing the modernization of Islamic education. One of the pesantren that follows the development of science and the progress of the times is the An-Nur 3 Islamic Boarding School. This Islamic boarding school provides primary, secondary, and high school education and has an advanced level of learning, a special program, namely the College of Classical Book (STIKK). This study aims to describe how the learning management of the classical book in STIKK An-Nur 3, from Lesson planning, Learning implementation, and Learning evaluation. This study uses a qualitative approach. The research data were taken by interview, observation, and documentation techniques. The results showed that this STIKK is the program of AN-Nur 3, which aims to teach the essence of the classical book more deeply than the previous madrasah levels. In learning the Classical book at STIKK, there is a planning, implementation, and evaluation process that supports learning activities to run effectively and efficiently. What distinguishes it from other educational programs is that students at STIKK, besides studying the yellow book, also study in a university that has an agreement with STIKK.